Syntheses of Highly Functionalized Spirocyclohexenes by Formal [4+2] Annulation of Arylidene Azlactones with Allenoates. Issue 8 (10th June 2018) - Eitzinger, Andreas; Zielke, Katharina; Widhalm, Michael; Robiette, Raphaël; Waser, Mario
Abstract: A straightforward phosphine‐catalyzed formal [4+2] annulation between α‐branched allenoates and arylidene azlactones has been developed to access highly functionalized spirocyclohexenes. This cyclization favors the γ‐addition of the phosphine‐activated allenoates over a β′‐addition pathway. Detailed computational studies support the proposed mechanism and provide a reasonable explanation for the observed regioselectivity and the noted effect of the catalyst. Abstract : A pinch of PBu3 : A phosphine‐catalyzed [4+2] annulation between α‐branched allenoates and arylidene azlactones has been developed to access highly functionalized spirocyclohexenes. EWG=electron‐withdrawing group.